The Issue of Judicial Consideration in Acquittal (Vrijspraak) : Cases of Sexual Violence Against Children - Novita Cahyaningrum; Gelar Ali Ahmad (Veteran Law Review, 2025)
Acts of sexual violence against children in Indonesia continue to rise each year. This situation is triggered by victims' fear of reporting and attempts by perpetrators to silence them, especially when perpetrators have certain powers or positions. This crucial phenomenon is evident in the acquittal of Case Number 329/Pid.Sus/2024/PN Jap. The panel of judges' considerations were based solely on Article 183 KUHAP without considering Article 25 TPKS Law. This study uses a normative juridical method through a literature study of primary and secondary legal sources, which are analyzed descriptively and qualitatively. The purpose of the study is to examine the basis for the judge's decision, which contradicts the objectives of the law, as well as the legal consequences and solutions. The results of the study show that the panel of judges relied more on general rules than specific rules, thereby contradicting the principles of Lex Specialis Derogat Legi Generali and Testimonium de auditu. Therefore, it is recommended that law enforcement officials and judges progressively update their understanding of the law and implement preventive and repressive legal protection measures so that acquittal do not become a form of impunity for criminals.